Using Andragogy Approach to Transfer Pancasila Values in Economic Learning - Nunuk Suryanti; Wahjoedi Wahjoedi; Sugeng Hadi Utomo; Agung Haryono; Nurhuda Nurhuda (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang)
According to an increasing number of business practices that tend to apply the economic system of capitalism, transferring Pancasila values in economic learning for the novice entrepreneur is quite essential to do. The amount of business competition everywhere erodes the values of togetherness and brotherhood that characterize the nation's culture. The Association of Micro Small and Medium Enterprises (MSME) in Indonesia is a supporting pillar in the learning of Micro Small and Medium Enterprises (MSME) that still prioritize the basis of Pancasila economy values such as cooperation, kinship, and mutual assistance. Thus, this review of literature aims to examine the educational approach that can transfer the values to adult students; that is andragogy. The discussion part mainly addresses the values of Pancasila, the economic learning through andragogy approach, and the characteristics of adult students. This review paper concludes that Andragogy approach can be effective to facilitate the process of transferring the values of Pancasila in the Micro Small and Medium Enterprises (MSME) in Indonesia.DOI: https://dx.doi.org/10.17977/UM014v13i22020p108